Status of Women In Agrarian Society: a Case Study of Women’S Land Rights, Gender and Agrarian Change: Examining the Marginalization of Women's Land Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The main objective of this paper is to contribute to theanalysis of the marginalization of women s. land rights in India bygovernmental institutions and rural women s. movements. In order tocontextualize this analysis, the paper presents the broader transformations ofthe Indian rural economy, principally over the last two decades, and the majorchanges that have occurred in the position of rural women as a result ofagricultural modernization. The question of women's land rights has a relativelyyoung history in India. This paper briefly traces that history before examiningwhy gendering the land question remains critical, and what the newpossibilities are for enhancing women's land access.